Strategi Optimalisasi Kemampuan Belajar Anak Berkebutuhan Khusus (ABK) melalui Program Pembelajaran Individual (PPI) - Hernik Farisia (Program Studi PGRA, 2017)
This article examines how to design Individual Learning Program (Program Pembelajaran Individual-PPI) to help students with special needs (Anak Berkebutuhan Khusus-ABK) to develop their potentials and to maximally resolve their learning problems. PPI is a learning program that has purpose to support ABK for being in inclusive class. The program is adapted from Individualized Educational Program (IEP) model –developed in America educational system- that contains of some learning events or programs to ABK for specific learning goal. One of inclusive schools that succeed developing PPI is Badrus Salam Islamic Elementary School, Surabaya. Based on PPI documents developed by Badrus Salam Islamic Elementary School team, steps for arranging PPI are: identifying strength, weak, characteristic and interest as the assessment on ABK, formulating specific information from assessment result to make students profiles that describe their need supports to increase students’ performance, designing learning method, and arranging evaluation method as indicator of students’ learning success. Whereas result shows that 75% ABK are able to optimize their learning ability indicated by their behaviour change. It is because teachers have some strategies to overcome it, such as: giving assignment regularly, designing media based on students’ characteristic, asking question related to learning process, and increasing teachers, peers, and parents’ role in learning process. From the explanation above, it is concluded that curriculum development in Badrus Salam Islamic Elementary School is in a standard manner, nonetheless there is special adaptation related to students’ individual needs.